Utilisation of Digital Video Media to Increase Learning Engagement of Al-Qur'an Hadith Learning in Madrasahs of Central Kalimantan - Rodhatul Jennah; Sigit Purnama; Surawan; Mazrur (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This research aimed to capture the student engagement and motivation in learning the Al-Qur’an Hadith  are often hindered by the abstract nature of religious material and the continued reliance on conventional instruction. This study aims to analyze the effectiveness of digital video media in increasing affective, cognitive, and behavioral engagement of students in Al-Qur'an Hadith learning at Madrasahs in Central Kalimantan. Design/methods/approach – This study employed a convergent parallel mixed-methods design, integrating quantitative and qualitative approaches. Quantitative data were collected from 155 students at MAN in Central Kalimantan using pre- and post-tests and analyzed through descriptive statistics, while qualitative data were obtained from interviews with five informants and analyzed thematically based on engagement indicators. Findings – The results show a significant improvement in students’ learning outcomes, with an average increase of 15.6% after the implementation of digital video media. This media enhances students’ motivation, focus, comprehension of abstract religious concepts, and multidimensional engagement, thereby improving the effectiveness and quality of Al-Qur’an Hadith instruction in digital learning environments. Research implications/limitations – The findings are context-specific to two Madrasahs in Central Kalimantan and may not be generalizable to all Islamic educational contexts. Variations in teachers’ digital literacy and students’ motivation levels may influence the effectiveness of implementation. Originality/value – This study offers empirical and pedagogical evidence on multimedia integration in Islamic education, demonstrating that digital video media enhances cognitive achievement as well as affective and behavioral engagement in Qur’an Hadith learning, thereby contributing a contextualized model for Islamic education in Central Kalimantan’s digital learning context